Stereospermum tetragonam as an antidiabetic agent by activating PPARγ and GLUT4 - Bino Kingsley; K. P. Arun; Stalin Selvaraj; Brindha Pemiah (Bangladesh Pharmacological Society, 2014)
Present study evaluates the anti-diabetic activity of S. tetragonam LC-MS/MS experiments showed the presence of two novel molecules C1 and C2, which were further taken for in silico study against PPARγ. Cell culture studies with A431 cells in the presence of crude aqueous extract showed the elevated level of PPARγ and GLUT4 and also confirmed using in silico studies. Thus, the present study proves the mecode of action of S. tetragonam as an antidiabetic drug.